INSENTIF PAJAK PENGHASILAN BAGI UMKM: REFORMASI, KERINGANAN DAN KEPATUHAN - Jerry Shalmont; Grace I. Darmawan; Dora Dominica (Justitia et Pax, 2022)
As a response to COVID-19, the Government issued some income tax incentives based on the Minister of Finance Regulation (MoF Regulation) No. 23/PMK.03/2020 concerning Tax Incentives for Taxpayers Who Suffered from COVID-19. There are six tax incentives given by the Government to the Taxpayer, one of them is PPh Final DTP UMKM. In 2021, the Government issued two MoF Regulations which extended the period until December 2021. Through Law Number 7 of 2021 concerning Harmonization of Tax Regulations (UU HPP), the incentive arrangement is adjusted once again. The research topic will focus on the utilization of tax incentives by taxpayers, in particular, the SMEs after the enactment of UU HPP. This research is normative research using regulatory and structural approaches. The research result shows that the reformation of PPh incentives for SMEs through the UU HPP is meant to 1) simplify and make a permanent facility that can be utilized by the SMEs; and 2) improve legal certainty as part of community support. However, this is not enough. The Government shall enact the implementing regulations of UU HPP to improve awareness and compliance of the SMEs to register their businesses and become the registered taxpayer.